Analysis Of E-Payment Applications: A Case Study Of One Of The Zakat Institutions In Malaysia - Nor Asiah Yaakub; Nathasa Mazna Ramli; Nurul Aini Muhamed; Izlawanie Muhammad (Universiti Tun Hussein Onn Malaysia, 2024)
Payment is the heart of businesses. For an online business, electronic-payment (e-payment) plays a significant role to expedite the transaction. Online or e-payment system is not crafted for business as merely profit-oriented but it isoffered to all, including government and other non-profit organisationinstitutions. Nowadays, it can be witnessed that there are various types of e-payment systems available to facilitate online selling and buying transactions. However, e-payment system at philanthropy institutions has received fairly little attention from the public. This is happening even though theseinst itutions have invested a lot of money on e-payment systems. Thus, this study attempts to identify types of e-payment systems at one of the Islamic philanthropic institutions in Malaysia and analyse the performance of e-payment in that institution. The result of this study is hoped to contribute to the body of knowledge particularly in terms of information technology and performance measurement in Islamic philanthropy institutions.